Formulation of mucoadhesive microspheres of rosiglitazone maleate and its in vitro evaluation using ionotropic gelation technique - Akanksha Garud; Navneet Garud (Facultad de Farmacia, Universidad de Granada, 2015)
Aim: The objective of the present study is to design and evaluate mucoadhesive microspheres for oral controlled release. Materials and Method: Rosiglitazone maleate microspheres with a coat consisting of alginate and a mucoadhesive polymer sodium carboxymethylcellulose, carbopol 934P and hydroxypropylmethylcellulose were prepared by an orifice-ionic gelation process. The microspheres were evaluated for FTIR studies, morphology, particle size, micromeritic properties, percentage entrapment efficiency, in-vitro wash-off test and in-vitro release studies. Results: The resulting microspheres were spherical and free flowing. The percent entrapment efficiency was 68.2 to 85.6%. The microspheres exhibited good mucoadhesive property in the in vitro wash-off test. Rosiglitazone release from these mucoadhesive microspheres was slow and extended over 12 h duration of time depending on the composition of coat. Conclusions: The prepared mucoadhesive microspheres are thus suitable for oral controlled release of Rosiglitazone maleate and thereby help in the management of type II diabetes mellitus.